Role of cytosolic and calcium independent phospholipases A2 in insulin secretion impairment of INS‐1E cells infected by S. aureus. Issue 24 (26th November 2015) - Caporarello, N.; Salmeri, M.; Scalia, M.; Motta, C.; Parrino, C.; Frittitta, L.; Olivieri, M.; Toscano, M.A.; Anfuso, C.D.; Lupo, G.
Abstract : Cytosolic PLA2 (cPLA2 ) and Ca 2+ ‐independent PLA2 (iPLA2 ) play a significant role in insulin β‐cells secretion. Bacterial infections may be responsible of the onset of diabetes. The mechanism by which Staphylococcus aureus infection of INS‐1 cells alters glucose‐induced insulin secretion has been examined. After acute infection, insulin secretion and PLA2 activities significantly increased. Moreover, increased expressions of phospho‐cPLA2, phospho‐PKCα and phospho‐ERK 1/2 were observed. Chronic infection causes a decrease in insulin release and a significant increase of iPLA2 and COX‐2 protein expression. Moreover, insulin secretion in infected cells could be restored using specific si RNAs against iPLA2 isoform and specific COX‐2 inhibitor. Abstract : Bacterial infections may be responsible for the onset of diabetes. S. aureus infection of INS‐1 cells alters glucose‐induced insulin secretion. Acute infection increases expressions of phospho‐cPLA2, ‐PKCα and ‐ERK 1/2. Insulin secretion in infected cells is restored by specific PLA2 ‐ si RNAs. Insulin secretion in infected cells is restored by a specific COX‐2 inhibitor.